2016
DOI: 10.1016/j.diagmicrobio.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2 chromogenic media for the detection of extended-spectrum β-lactamase producing Enterobacteriaceae stool carriage in nursing home residents

Abstract: ChromID ESBL agar and Brilliance ESBL agar were compared for the isolation of extended-spectrum β-lactamase (ESBL)–producing Enterobacteriaceae from 298 stools. These had comparable sensitivity and selectivity for the 116 positive samples. Pre-enrichment with cefpodoxime and extending incubation to 48 hours after direct plating both significantly increased sensitivity but reduced selectivity of both agars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 10 publications
3
12
0
Order By: Relevance
“…The sensitivity of Brilliance ESBL agar was higher than that observed in this study but vice versa. Our study showed increased sensitivity (97.8%) at 48 h on Brilliance ESBL agar, this correlates with Biane et al [28] study in Cambridge shire. Biane et al [28] reported an increase in sensitivity of Brilliance ESBL agar from 59% to 68% after 48 h incubation time.…”
Section: Fig 3 Culture Plate Of Clinical Isolate Of Escherichia Coli From Urine Showing Distinctive Blue Colony Colouration On Brilliancesupporting
confidence: 93%
“…The sensitivity of Brilliance ESBL agar was higher than that observed in this study but vice versa. Our study showed increased sensitivity (97.8%) at 48 h on Brilliance ESBL agar, this correlates with Biane et al [28] study in Cambridge shire. Biane et al [28] reported an increase in sensitivity of Brilliance ESBL agar from 59% to 68% after 48 h incubation time.…”
Section: Fig 3 Culture Plate Of Clinical Isolate Of Escherichia Coli From Urine Showing Distinctive Blue Colony Colouration On Brilliancesupporting
confidence: 93%
“…(), we used a semi‐selective enrichment step prior to plating on selective ESBL agar, which may have affected the recovery rate. The difference in the performance of semi‐selective (using broth selecting for Gram negative rods) and selective enrichment (i.e., broth additionally containing a third‐generation cephalosporin) remains to be elucidated and comparative data are limited (Blane et al., ; Jazmati, Hein, & Hamprecht, ; Kluytmans‐Van Den Bergh et al., ).…”
Section: Antimicrobial Resistant Escherichia Coli Obtained By Nonselementioning
confidence: 99%
“…Likewise, Jazmati et al (2017) showed the added value of an enrichment step for the screening of broad-spectrum cephalosporins-resistant Enterobacterales. In another study, an enrichment step was shown to increase the sensitivity of detection of ESBL-E from 75% to 97% in stool samples (Blane et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Aliquots of 100 μL of the stool suspension spiked with ESBL-E were inoculated a) directly onto chromID ESBL agar (bioMérieux), b) into 5 mL of nonselective TS broth, or c) into 5 mL of TS broth with cefotaxime (Acros Organics, Chemie Brunschwig AG, Switzerland) at 0.1 or 0.5 μg/mL (Blane et al, 2016) . Aliquot of 100 μL of the fecal suspension without the addition of ESBL-E directly spread onto chromID ESBL agar (bioMérieux) was used as a negative control.…”
Section: Spiking Experimentsmentioning
confidence: 99%